Integration of Financial Capability and The Economy of North Sumatra (Panel Regression Model) - Rusiadi; Lia Nazliana Nasution; Anisah Siregar; Abdiyanto; Dewi Mahrani Rangkuty; Nasib (International Forum of Researchers and Lecturers, 2023)
The district or province's financial capacity to integrate with the economy. The greater the contribution to the economic progress of North Sumatra. The research establishes regional financial integration (Local Revenue, asset spending, and General Allocation Fund) on North Sumatra's economic ability to develop development potential. The data analysis method uses panel data. The research results found that Local Revenue, asset spending, and General Allocation Funds simultaneously or together had an effect on the economy. Local Revenue and asset spending have a partial effect on the economy. The General Allocation Fund has no partial effect on the economy.